2021
DOI: 10.18549/pharmpract.2021.2.2426
|View full text |Cite
|
Sign up to set email alerts
|

An ounce of prevention is worth a pound of cure: considerations for pharmacists delivering the National Diabetes Prevention Program

Abstract: Prediabetes is highly prevalent in the United States affecting over 88 million adults. In 2010, the Centers for Disease Control and Prevention (CDC) established the National Diabetes Prevention Program (NDPP), an intensive lifestyle program consisting of a 16-lesson curriculum focused on diet, exercise, and behavior modification, with the ultimate goal to reduce progression from prediabetes to diabetes. Despite tens of millions of adults potentially qualifying to participate in the program, the uptake of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…A mixed-methods study of individuals with prediabetes conducted in England found that respondents found community pharmacies as an acceptable setting to receive diabetes prevention services and was preferred among those who regularly use a pharmacy and who had work and social commitments. 13 Importantly, CDC recognizes pharmacists as important partners to promote screening for prediabetes and diabetes, referring patients to NDPP, or delivering NDPP themselves, 14 yet the available evidence supporting the effectiveness of pharmacist-delivered NDPP is quite limited, with no evidence of program effectiveness reported in the community pharmacy setting. Overall, 34% of community pharmacies reported that more than half of their participants achieved at least 5% weight loss goal.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed-methods study of individuals with prediabetes conducted in England found that respondents found community pharmacies as an acceptable setting to receive diabetes prevention services and was preferred among those who regularly use a pharmacy and who had work and social commitments. 13 Importantly, CDC recognizes pharmacists as important partners to promote screening for prediabetes and diabetes, referring patients to NDPP, or delivering NDPP themselves, 14 yet the available evidence supporting the effectiveness of pharmacist-delivered NDPP is quite limited, with no evidence of program effectiveness reported in the community pharmacy setting. Overall, 34% of community pharmacies reported that more than half of their participants achieved at least 5% weight loss goal.…”
Section: Discussionmentioning
confidence: 99%